Behavioral Intentions of Online Zakat Users in Indonesia: An Extended TAM with Trust and Security - Supriyono Supriyono; Lili Supriyadi; Yunia Silvia Sesunan; Ela Patriana (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
Digital religious philanthropy in Indonesia has expanded the use of online zakat platforms, yet the determinants of user behaviour remain unclear. This study extends the Technology Acceptance Model (TAM) with trust and security to examine the behavioural intention and actual use of online zakat services. Data were collected from an exploratory sample of 120 Indonesian users recruited through purposive sampling and analysed with Partial Least Squares Structural Equation Modelling (PLS-SEM). Perceived usefulness and perceived security significantly predict behavioural intention, which in turn predicts actual use; perceived ease of use shows an unexpected negative association, while trust is not significant at conventional levels. The model explains 38.2 per cent of the variance in behavioural intention. Because the sample is small and urban-skewed, the results are exploratory and not nationally generalisable. The study contributes a religiously contextualised extension of TAM and a practical ordering of priorities for zakat institutions. Digitalisasi filantropi keagamaan di Indonesia memperluas penggunaan layanan zakat daring, namun determinan perilaku penggunanya belum sepenuhnya jelas. Studi ini memodifikasi Technology Acceptance Model (TAM) dengan menambahkan variabel kepercayaan (trust) dan keamanan (security) untuk mengkaji intensi perilaku dan penggunaan aktual layanan zakat daring. Data dikumpulkan dari sampel eksploratif 120 pengguna di Indonesia yang dipilih secara purposif dan dianalisis dengan Partial Least Squares Structural Equation Modeling (PLS-SEM). Persepsi kegunaan dan keamanan berpengaruh signifikan terhadap intensi perilaku, dan intensi perilaku selanjutnya memprediksi penggunaan aktual; persepsi kemudahan berpengaruh negatif yang tidak terduga, sementara kepercayaan tidak signifikan pada taraf konvensional. Model menjelaskan 38,2 persen varians intensi perilaku. Karena sampel berukuran kecil dan terkonsentrasi di perkotaan, temuan bersifat eksploratif dan tidak dapat digeneralisasi secara nasional. Studi ini menyumbang perluasan TAM yang terkontekstualisasi secara keagamaan serta prioritas praktis bagi lembaga zakat.